TINDAK PIDANA TRAFFICKING MENURUT HUKUM POSITIF DAN HUKUM ISLAM (SUATU ANALISIS PERBADINGAN HUKUM) - Ruslan Abdul Gani (Universitas Batanghari Jambi, 2017)
This study discusses the criminal acts of Trafficking according to positive law and Islamic law (an analysis of comparative law). As for the problem that dibahan among others How positive law and Islamic law Against Trafficking and the Trafficking problem in the settings How the view of the second law. From the results obtained from studies that both positive law and Islamic law looked Against Trafficking is a form of offence that constitutes crimes against humanity. Setting the problem Trafficking in view of the positive law can be found in Act No. 21 of 2007 of Traffiking, whereas in view of Islamic law is set out in the Qur'an and the Hadith, the Prophet, where Islam is said to be opposed to slavery itself.Keyword : Trafficking, Positive law, Islamic law